1998
DOI: 10.1111/j.1440-1681.1998.tb02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol Decreases Body Temperature by Reducing 5 Hydroxytryptamine Release in the Rat Hypothalamus

Abstract: 1. The effects of magnolol, isolated and purified from the cortex of Magnolia officinalis Rehd. et Wils, on thermoregulation and hypothalamic release of 5-hydroxytryptamine (5-HT) by in vivo microdialysis were assessed in normothermic rats and in febrile rats treated with interleukin-1 beta. 2. Intraperitoneal administration of magnolol (25-100 mg/kg) produced a decrease in colon temperature, an increase in foot skin temperature, a decrease in metabolic rate and a decrease in the endogenous release of 5-HT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The lectin from Pinellia ternate raise [Ca 2 + ]i by promoting Ca 2 + influx, and then facilitate neurotransmitter release (Shi et al, 1994). Magnolol and honokiol are known central nervous system depressants which can modulate central serotonergic activity (Hsieh et al, 1998;Kuribara et al, 1998;Tsai et al, 1995). Magnolol and honokiol are also reported to inhibit MDA production in rat heart mitochondria (Lo et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…The lectin from Pinellia ternate raise [Ca 2 + ]i by promoting Ca 2 + influx, and then facilitate neurotransmitter release (Shi et al, 1994). Magnolol and honokiol are known central nervous system depressants which can modulate central serotonergic activity (Hsieh et al, 1998;Kuribara et al, 1998;Tsai et al, 1995). Magnolol and honokiol are also reported to inhibit MDA production in rat heart mitochondria (Lo et al, 1994).…”
Section: Discussionmentioning
confidence: 95%
“…In the previous experimental studies, we found that Banxia-Houpu decoction exhibited antidepressant-like properties via regulation of the central neurochemical and immune responses in well-validated models of depression in rodents (Li et al, 2003a,b;Guo et al, 2004;Zhang et al, 2004;Wang et al, 2005). Honokiol and magnolol, the major constituents simultaneously identified in magnolia bark (Teng et al, 1988), are considered to be central nervous system depressants that modulate the central serotonergic activity (Tsai et al, 1995;Hsieh et al, 1998;Kuribara et al, 1998). Our previous study also confirmed that the mixture of honokiol and magnolol (HMM) were the active principles responsible for antidepressant activity of magnolia bark .…”
Section: Introductionmentioning
confidence: 97%
“…MBE is consumed for the relief of menopausal symptoms, for increasing metabolism, and for reducing cortisol levels. Historically, magnolia bark has been used for many years as a component of traditional Chinese medicines and Japanese remedies for the treatment of depression, anxiety, nervous disorders, gastrointestinal disturbances, asthma, and stroke, as well for the alleviation of headaches, muscular pain and fever (Hattori et al, 1986;Tsai et al, 1995;Ogata et al, 1997;Sarker, 1997;Hsieh et al, 1998;Maruyama et al, 1998). The mechanism for the purported biological activity of MBE is unclear; however Homma et al (2000) and Hsu et al (2004) have reported that magnolol (the main constituent of MBE) can reduce eicosanoid mediator levels, and the anti-inflammatory and anti-asthmatic effects may be related to MBE's antibacterial activity (Bensky and Gamble, 1993).…”
Section: Introductionmentioning
confidence: 99%